Research on Divorce Cooling-off Period System in China - Zhang, Feifei (International Journal of Social Sciences and Public Administration, 2024)
Along with the economic prosperity of the 21st century, there is also a progressive concept of marriage. In the pursuit of "new Under the marriage freedom of the era, whether the quality of their own marriage life has become the most important for economically independent couples Heavy place. However, recent years, economic development, social change, and the change of people's ideology, the number of divorce in our country has been increasing, the divorce rate has gradually gone higher, people's confidence in marriage has also decreased. In order to reduce the divorce rate, reduce the phenomenon of impulsive divorce, and maintain family harmony and social stability, China has stipulated a cooling-off period system for divorce. The divorce cooling-off period system is a new system in our country, which has played positive functions in many aspects. However, the system still has some shortcomings, such as the divorce cooling-off period personal safety protection, property protection and the protection of the rights and interests of minor children, etc. Then the necessary in-depth analysis is carried out and more perfect suggestions are put forward to make the system to assume its social and legal functions.